Tensile properties of open hole and unhole sugar palm ‘Ijuk’ (SPI) fibre composite treated with sodium hydroxide (NaOH) / Jamaliah Md Said ... [et al.] - Md Said, Jamaliah; Jumahat, Aidah; Mahmud, Jamaluddin; Chalid, Mochamad (UiTM Press, 2024)
This study evaluates the effects of sodium hydroxide (NaOH) treatment on tensile properties of sugar palm 'ijuk' (SPI) fibre-reinforced polymer (FRP) composites, with and without an open hole that acts as a stress concentrator. The NaOH treatment is aimed to improve the interfacial adhesion between SPI fibres and polymer matrix. Composite specimens were prepared using the hand lay-up method, incorporating SPI fibres in various orientations, and featuring a 6 mm diameter hole. Tensile tests were conducted to evaluate the mechanical performance of SPI FRP composite, including ultimate tensile strength, Young's modulus, and elongation at break. The research also compared the properties of SPI to those of synthetic glass fibre in fibre-reinforced polymer composites. The results showed that NaOH treatment significantly improves the fibre-matrix adhesion with 26% increase in tensile strength, leading to enhanced tensile properties in both samples, regardless of hole presence. The 0° orientation provides the highest strength and stiffness when the load is applied in the direction of the fibres. While for the 90° orientation, strength reduces by 14%. The impact of the hole on stress concentration and the subsequent mechanical behaviour of the open-hole specimens is substantial. The findings of this study offer insightful perspectives on the potential use of NaOH-treated SPI fibre in structural and other applications, demonstrating its ability to withstand tensile stresses, even with geometric discontinuities like holes.